UK public reaction to carbon dioxide transport and temporary storage at ports - Feetham PM; Wright MJ; Carlisle D; Konopka R; Teagle DAH (Springer Nature B.V., 2025)
Achieving net zero carbon dioxide emissions will require investment in large-scale logistical infrastructure to remove, transport, and store carbon dioxide from the atmosphere, exhaust gases, and waste streams from industrial plants. Successful implementation of carbon capture, storage (CCS) will depend on stakeholder investment and public agreement. Evidence of how the public perceive methods of CCS and their preferences among potentially viable options remains scarce. To gain knowledge of likely public reaction we elicited perceptions of CCS and transport, as well as preferences for different CCS capture, storage, transport, and regulation options, via a UK representative on-line survey (n = 1070). Compared to three other industrial substances (hydrogen, ammonia and LNG) perceptions of transport and storage of carbon dioxide were somewhat favourable, indicating public reaction towards carbon dioxide shipping and temporary storage at ports is moderate, reducing the likelihood of major controversy. When considering preferences for alternative CCS and transport options, the most important factors of those evaluated were Regulation and Transport. The most preferred approach involved international or government regulation and pipeline transport, with industry self-regulation receiving the least support. These findings suggest the use of pipelines or where necessary ships and either international or government regulation are promising pathways to increase the chances of public acceptance of CCS.
Keywords: Carbon capture storage and transport; Carbon dioxide transport via pipelines and ships; Port storage of industrial substances; Public perceptions of CCS options